2021
DOI: 10.1111/1751-7915.13807
|View full text |Cite
|
Sign up to set email alerts
|

Armeniaspirol A: a novel anti‐Helicobacter pylori agent

Abstract: Antibiotic resistance in Helicobacter pylori has been growing worldwide with current treatment regimens. Development of new compounds for treatment of H. pylori infections is urgently required to achieve a successful eradication therapy in the future. Armeniaspirols, a novel class of natural products isolated from Streptomyces armeniacus, have been previously identified as antibacterial agents against Gram-positive pathogens. In this study, we found that armeniaspirol A (ARM1) exhibited potent antibacterial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Moreover, a combination of ARM1 and omeprazole more effectively killed H. pylori in vivo compared to standard triple therapy in a mouse model of multidrug-resistant H. pylori infection. 12 The combination of DHT and omeprazole also showed superior H. pylori -killing effect than standard triple therapy, suggesting that DHT may be suitable anti- H. pylori drug when combined with a proton pump inhibitor. 57 From the above, it follows that natural products have great potential to combat H. pylori biofilms and to address the problem of drug resistance in H. pylori .…”
Section: Anti-biofilm Agents Against H Pylorimentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, a combination of ARM1 and omeprazole more effectively killed H. pylori in vivo compared to standard triple therapy in a mouse model of multidrug-resistant H. pylori infection. 12 The combination of DHT and omeprazole also showed superior H. pylori -killing effect than standard triple therapy, suggesting that DHT may be suitable anti- H. pylori drug when combined with a proton pump inhibitor. 57 From the above, it follows that natural products have great potential to combat H. pylori biofilms and to address the problem of drug resistance in H. pylori .…”
Section: Anti-biofilm Agents Against H Pylorimentioning
confidence: 97%
“…Majority of H. pylori strains are capable of forming biofilms in vivo and in vitro depending on the strain. 11 , 12 Clinical strains isolated from the gastric mucosa of patients have been reported to have higher capacity to form biofilm than other strains. 13 The formation of biofilms by H. pylori , like other bacteria, is divided into four steps: (1) attachment, (2) growth, (3) maturity, and (4) dispersal ( Figure 1 ).…”
Section: Helicobacter Pylori Biofilmmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature, 7-O-butylnaringenin (flavonoid) decreased the viable cell count of H pylori strains in 2 log units (Moon et al, 2013). Besides, armeniaspirol A, a product isolated from Streptomyces armeniacus led to a three-log decrease in viable cell count of H. pylori strains (Jia et al, 2022). On the other hand, we performed both optical and electron microscopy of treated and untreated H. pylori cells with asclepain cI.…”
Section: E Ects Of Subinhibitory Concentrations (Submics) Of Asclepai...mentioning
confidence: 99%
“…A recent study reported in vivo efficacy of 1 in a Helicobacter pylori mouse infection model, and the disruption of the H. pylori cell membrane was observed by electron microscopy after treatment with 1. 8 However, the understanding of armeniaspirol's activity has been hampered by the fact that their mechanism of action has been still unknown. Intriguingly, while we drafted this manuscript, Labana et al published the interaction of the armeniaspirol derivative 4 with the proteases ClpXP and ClpYQ – a mechanism that is different to the ones we report below (see discussion).…”
Section: Introductionmentioning
confidence: 99%